2020
DOI: 10.1002/adfm.202004613
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances of Emerging 2D MXene for Stable and Dendrite‐Free Metal Anodes

Abstract: Metal anodes based on a plating/stripping electrochemistry such as metallic Li, Na, K, Zn, Mg, Ca, Al, and Fe have attracted widespread attention over the past several years because of their high theoretical specific capacity, low electrochemical potential, and superior electronic conductivity. Metal anodes can be paired with cathodes to construct high-energy-density rechargeable metal batteries. However, inherent issues including large volume changes, uncontrollable growth of dangerous dendrites, and an unsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
94
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 172 publications
(101 citation statements)
references
References 227 publications
(287 reference statements)
0
94
0
Order By: Relevance
“…When excess ZnCl 2 is used, a Cl-terminated MXene is obtained, like Ti 2 CCl 2 and Ti 3 C 2 Cl 2 . Thus, these Lewis acidic melts could etch Al from MAX phases providing a variety of MXene based on redox-controlled mechanisms [ 43 ]. It is found that the lattice parameters of MXene etched by salt are greater than the one etched by acid and the layer spacing is also increased in salt-etched MXene [ 44 ].…”
Section: Synthesis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When excess ZnCl 2 is used, a Cl-terminated MXene is obtained, like Ti 2 CCl 2 and Ti 3 C 2 Cl 2 . Thus, these Lewis acidic melts could etch Al from MAX phases providing a variety of MXene based on redox-controlled mechanisms [ 43 ]. It is found that the lattice parameters of MXene etched by salt are greater than the one etched by acid and the layer spacing is also increased in salt-etched MXene [ 44 ].…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…In this process Cl - rapidly etch Al because of its strong binding ability. The cations intercalate and increase the d-spacing [ 43 ].…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…An ideal Li host should be 1) lightweight, robust, and porous to accommodate Li; 2) electrochemically stable during the Li plating/stripping processes; 3) highly conductive and has low Li + diffusion energy barrier to achieve rapid electrochemical kinetics; and 4) lithiophilic to guarantee the efficient combination with Li and guide its nucleation. [ 12 ]…”
Section: Challenges and Solutions Of Lithium–sulfur Batteriesmentioning
confidence: 99%
“…Great efforts have been made in recent decades to overcome these problems, including physically confining sulfur in porous carbons, [ 6a,9 ] chemically bonding LiPSs by polar metal compounds, [ 10 ] inserting a conductive interlayer between cathode and separator, [ 11 ] and designing advanced Li anode to suppress the dendrite growth. [ 12 ] Based on these strategies, the above‐mentioned issues are somewhat mitigated, but the Li–S batteries’ commercial application has not yet been realized.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 2D materials, such as graphene, [ 14 ] h‐BN, [ 15 ] and MXenes, [ 16 ] have been investigated as scaffolds or substrates for Li metal anodes. Especially, 2D transition metal carbides known as MXenes have attracted attention in capacitor and battery research due to their metallic electrical conductivity, [ 17 ] exceeding that of solution processed graphene.…”
Section: Introductionmentioning
confidence: 99%